Rezolvati ecutiile:
(x+3)*(x-3)+5(2x-1)=(x+3)*(x-2)+5x-10
10-2(x-1)²=3(x-1)-(x-2)*(2x+1)

Multumesc

2
a)x²-9 +10x -5 = x² - 2x +3x - 6 +5x -10
x² +10x -14 = x ² +4x -16
x² - x² +10x - 4x = 14 - 16
6x = -2
x = -2/6
x = -1/3

b) 10 - 2 (x² -2x +1) = 3x -3 - (2x² +x -4x -2)
10 -2x² -4x -2 = 3x -3 -2x² -x +4x +2
-2x² -4x + 8 = -2x² +6x -1
-2x² + 2x² -4x -6x = -1 -8
-10x = -9
10 x =9
x = 9/10

Răspunsuri

Cel mai inteligent răspuns!
2014-04-28T20:22:43+03:00
A)x²-9 +10x -5 = x² - 2x +3x - 6 +5x -10
x² +10x -14 = x ² +4x -16
x² - x² +10x - 4x = 14 - 16
6x = -2
x = -2/6
x = -1/3

b) 10 - 2 (x² -2x +1) = 3x -3 - (2x² +x -4x -2)
10 -2x² -4x -2 = 3x -3 -2x² -x +4x +2
-2x² -4x + 8 = -2x² +6x -1
-2x² + 2x² -4x -6x = -1 -8
-10x = -9
10 x =9
x = 9/10
1 5 1
2014-04-28T20:22:53+03:00
X²-9+10x-5=x²-2x+3x-6+5x-10⇒10x+2x-3x-5x=5+9-6-10⇒12x-8x=14-16⇒4x=-2⇒x=-1/2